Technology Addiction in the Digital Economy and Suggested Solutions - Ertemel, Adnan Veysel; Aydın, Gökhan (Addicta: The Turkish Journal on Addictions, 2018)
This study argues that technology addiction is a natural consequence of current digital ecosystem characterized with attention economy. The fact that technology platforms architect addictive experiences by exploiting weaknesses of human brain results in consumers’ spending prolonged periods of time on screens. To remedy this problem, this paper proposes various solutions and best practices using a comprehensive approach. Proposals at individual level, family level, organization level and ultimately societal and governmental level are discussed, in order, to overcome technology addiction problem.Citation: Ertemel, A. V., & Aydın, G. (2018). Technology addiction in the digital economy and suggested solutions. Addicta: The Turkish Journal on Addictions, 5, 665−690. http://dx.doi.org/10.15805/addicta.2018.5.4.0038
Keywords: Technology addiction; Attention economy; Internet addiction; Online addiction